Interferensi Bahasa Bugis terhadap Penggunaan Bahasa Indonesia Siswa SMP dalam Berkomunikasi - Sriwahyuni Sriwahyuni; Ahmad Ghazali Samad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2021)
Based on circumstances that require that in the process of learning a good language, the language must be in accordance with the rules. However, in reality, Indonesian language errors are still often found in schools. The reason is language acquisition and mastery of more than one language (bilingual). Therefore, the purpose of this study is to describe the form of Bugis language interference on the use of Indonesian used by students. The method used in this study is a qualitative descriptive method. Data collection techniques in this study used direct dialogue with students, observing students in communicating (in the learning process). The result of this research is that there is a tendency for students of SMP Negeri 1 Pammana to interfere with Bugis language when communicating or speaking in Indonesian, this is done even in formal situations.